Evaluating Moral Judgment Abilities Using the ONYX Technique: Testing and First Results - Fedor Kozyrev (Voprosy obrazovaniya / Educational Studies Moscow, 2013)
Fyodor Kozyrev, D.Sc. in Pedagogy, Professor at the Russian Christian Humanities Academy, Director of the Institute of Religious Pedagogy, Russian Christian Humanities Academy, Saint Petersburg, Russian Federation. Email: fedorkozyrev@yandex.ru Address: 15 Fontanki Quay, Saint Petersburg, 191023, Russian Federation.The paper includes description of the new ONYX testing technique allowing for standardized quantitative assessment of moral judgment abilities. The technique was developed by improving Lind’s standardized version of Kohlberg dilemma method (Moral Judgment Theory).Testing results prove high efficiency of the ONYX technique in solving diagnostic tasks related to monitoring moral education at school. The tests have shown that the technique is surely efficient in the amount of information obtained per unit of time. The author argues that the method can be applied to perform standardized tests among school students of all ages, beginning as early as with the fifth grade and until graduation. The revealed dramatic difference in results across classes may serve an indirect proof of efficiency of teaching measures to accelerate moral development of children. From a methodical point of view, high differentiation of average indicators across high school classes allows to use the technique to assess effectiveness of educational programs, performance of teachers and collective achievements of individual classes and schools. The testing technique has also turned out to reveal latent abilities of students.A comparison of data collected from different age groups has shown that the measured combined indicator of moral selectivity and coherence may serve a measure of moral development. This indicator has a statistically proven advantage over the competency index applied by foreign researchers. The ONYX technique includes additional analysis tools allowing for a detailed diagnosis of specific features of moral motivation.